Exposing bovine cumulus–oocyte complexes to aromatizable androgen restore serum-induced low estradiol production in vitro. Issue 4 (November 2014) - Bernuci, M.P.; Bulgareli, D.L.; Vireque, A.A.; Pitangui, C.P.; de Sa, M.F.S.; Rosa-e-Silva, A.C.J.S.
Summary We aimed in this study to assess whether serum-decreased bovine cumulus–oocyte complex (COC) steroidogenesis during in vitro maturation (IVM) is caused by deficient androgen milieu. For this approach, bovine COCs were cultured in serum-supplemented IVM medium in the presence or absence of 1 μM androstenedione. After 24 h of culture, medium was collected and analyzed for its content of estradiol-17β (E2) and progesterone (P4). Medium E2 content markedly increased after incubation of COCs with androstenedione (17.52 ± 1.86 ng/ml to the androgen group; 0.32 ± 0.05 ng/ml to the non-androgen group). No significant difference in the P4 content was detected despite the presence of androstenedione (21.83 ± 1.61 ng/ml to the androgen group; 21.73 ± 1.67 ng/ml to the non-androgen group). Our data provide compelling evidence that bovine COCs steroidogenesis remains functional during culture in serum-supplemented medium and suggest that serum-induced decreased COCs estradiol secretion is caused by deficiency of an aromatizable androgen source.